Building a Mathematical Model for the Optimal Design of Pumping Stations Sewage Suction Basins Using Characteristic Method - عز الدين حسن; هبة عفوف (Latakia University Journal -Engineering Sciences Series, 2022)
Drainage systems in some parts, such as collection basins, may contain regulators to regulate the water level in these basins. During the work of the pumping groups, an unstable flow movement arises, because the influx of sewage water is not fixed, but always changing. These unstable flows are studied by relying on modern numerical methods such as the network-variable characteristics method. This method gave satisfactory and good results in calculating these flows in an absorption basin of a pumping station located on a sewage collector at Jeresha station in Lattakia, and to test the dimensions of this basin. So that the pumps work optimally and in accordance with the water level in the basin with the ideal design dimensions, and the optimum time period was reached between two pumps taking off, as well as between two stops, thus choosing the optimal pumps and the economic dimensions of the basin. The calculation was done with the help of c sharp programs.